Dietary Aflatoxin B1 attenuates immune function of immune organs in grass carp (Ctenopharyngodon idella) by modulating NF-κB and the TOR signaling pathway - He, Xiang-Ning; Zeng, Zhen-Zhen; Wu, Pei; Jiang, Wei-Dan; Liu, Yang; Jiang, Jun; Kuang, Sheng-Yao; Tang, Ling; Feng, Lin; Zhou, Xiao-Qiu (Frontiers in Immunology, 2022)
Aflatoxin B1 (AFB1) is kind of a common mycotoxin in food and feedstuff. Aquafeeds are susceptible to contamination of AFB1. In teleost fish, the spleen and head kidney are key immune organ. Moreover, the fish skin is a critical mucosal barrier system. However, there was little study on the effects of dietary AFB1 on the immune response of these immune organs in fish. This study aimed to explore the impacts of oral AFB1 on the immune competence and its mechanisms in the skin, spleen, and head kidney of grass carp. Our work indicated that dietary AFB1 reduced antibacterial compounds and immunoglobulins contents, and decreased the transcription levels of antimicrobial peptides in grass carp immune organs. In addition, dietary AFB1 increased the transcription levels of pro-inflammatory cytokines and reduced the transcription levels of anti-inflammatory cytokines in the grass carp immune organs, which might be regulated by NF-κB and TOR signaling, respectively. Meanwhile, we evaluated the content of AFB1 in the grass carp diet should not exceed 29.48 μg/kg diet according to the levels of acid phosphatase and lysozyme. In summary, dietary AFB1 impaired immune response in grass carp skin, spleen, and head kidney.